Environmental Factors in the Growth of Jatropha at Potorono Village, Yogyakarta - Mohammad Nurcholis; S Sumarsih; R. R. R. Brotodjojo; D. Haryanto (Faculty of Agriculture, Universitas Sebelas Maret, 2015)
Jatropha curcas is a perennial crop that has been known by Indonesian people for more than seven decades as a plant that produces renewable biofuel. In the present decade, plants producing biofuel are expected to be developed to overcome the lowering nonrenewable fuel reserves. There is a myth that jatropha can grow well on marginal lands and draught condition, perform well on non-fertile soils, no need for agronomic management and is resistant to plant pests and diseases. This study was conducted to identify the environmental factors that influenced the growth of jatropha on the marginal land at Potorono village, Yogyakarta Province, Indonesia. Jatropha has been planted by local people at the village road sides and on the marginal land field at the local governmental land in this village. They grew jatropha on these areas with the purpose of preventing competition of area utilization with food crops. The results showed that the growth of jatropha was restricted by low content of organic matter, plant nutrition and poor soil drainage. Applications of manure and macro nutrients (N, P and K) to this crop were able to increase crop performance. The number of shoots, flowers and fruit bunches increased by manure and nutrients treatments. Field observation showed that there were several plant pests, such as Aspidiotus sp., Paracoccus marginatus, Poliphagotarsonemus latus, Selenothrips rubrocinctus, Chrysochoris javanus, Valanga nigricornis, Chloracris prasina, and Helicoverpa armigera that attacked plant leaves and fruits. There were plant leaf necrotic symptoms that caused by plant pathogens were also observed. The diseases are bacterial leaf spot (Xanthomonas ricinicola), cercospora leaf spot (Cercospora ricinella) and rust (Phakopsora jatrophicola). Thus, jatropha is like any other plants that need a good agro-ecological condition to grow well and produce high yield.